Einstein the penguin - Rangeley, Iona (HarperCollins Children's Books, 2021)
When the Stewarts spend a sunny, frosty December day at London Zoo, they're enchanted by one small penguin. At the delight of young Imogen and Arthur, Mrs Stewart insists the penguin must come and stay with them whenever he likes. But not one Stewart expects the penguin to turn up at their door that evening, rucksack labelled Einstein on his back... The family's new feathered friend helps Arthur to come out of his shell and makes massive demands on Imogen's amateur sleuthing. But together they must find out why Einstein came to them and they must keep away from the mysterious white-coat man. And Einstein can't stay forever, can he...? From stunning new writing talent Iona Rangeley, and illustrated with wit and brio by the award-winning David Tazzyman, this is a book that will be treasured for years to come
Keywords: Freundschaft; Familie; Pinguine; Penguins / Juvenile fiction; Friendship / Juvenile fiction; Animals / Juvenile fiction; Manchots (Oiseaux) / Romans, nouvelles, etc. pour la jeunesse; Amitié / Romans, nouvelles, etc. pour la jeunesse; Kinderbuch